1995
DOI: 10.1038/sc.1995.29
|View full text |Cite
|
Sign up to set email alerts
|

The management of upper urinary tract calculi by piezoelectric extracorporeal shock wave lithotripsy in spinal cord injury patients

Abstract: , 15 spinal cord injury patients were treated by piezoelectric extracorporeal shock wave lithotripsy. Aged from 23 to 71 years (mean = 39), they presented with a total of 23 stones, of which 18 were located in the calyces, three in the renal pelvis and two in the proximal ureter. The maximum dimensions of calculi varied from 5 to 35 mm (mean = 11). Patients were placed in a dorsal decubitus position during the sessions, three being sedated with diazepam, while the other 12 remained unsedated.All were treated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Furthermore, because of positioning problems related to the potential kyphoscoliosis and pelvic tilt, and consequent difficulties in the accurate location of shock‐waves on renal calculi for lithotripsy, these patients might be at greater risk of developing renal parenchymal and vascular damage after ESWL [19]. The potential long‐term effects on renal parenchyma dictate strict control of its repeated use [18]. Other common issues that arise with ESWL are the elimination of stone fragments that can cause obstruction, and incomplete stone clearance permitting ongoing infection and nephrolithiasis [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, because of positioning problems related to the potential kyphoscoliosis and pelvic tilt, and consequent difficulties in the accurate location of shock‐waves on renal calculi for lithotripsy, these patients might be at greater risk of developing renal parenchymal and vascular damage after ESWL [19]. The potential long‐term effects on renal parenchyma dictate strict control of its repeated use [18]. Other common issues that arise with ESWL are the elimination of stone fragments that can cause obstruction, and incomplete stone clearance permitting ongoing infection and nephrolithiasis [18].…”
Section: Discussionmentioning
confidence: 99%
“…The potential long‐term effects on renal parenchyma dictate strict control of its repeated use [18]. Other common issues that arise with ESWL are the elimination of stone fragments that can cause obstruction, and incomplete stone clearance permitting ongoing infection and nephrolithiasis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least six case series describing SWL in a cohort of patients with SCI have been published (Level 4). [18][19][20][21][22][23] There are no more contemporary series than those in the late 1990s and all have relatively small numbers of patients (see Tables 1-3). No case control or comparative trial was identified.…”
Section: Presentation Of Stone Disease In Sci Patientsmentioning
confidence: 99%
“…Kabalin et al 54 reported that without anesthesia 19 out of the 20 individuals developed AD during ESWL. In another study conducted by Robert et al 55 using piezoelectric ESWL, only 3 out of the 11 individuals received sedation and yet no episodes of AD occurred in any individuals. Stowe et al 31 reported that 6 out of the 22 cervical SCI patients with spinal anesthesia developed AD.…”
Section: Cystoscopy and Transurethral Litholapaxymentioning
confidence: 99%